A collaborative strategy for stable lithium metal anodes by using three-dimensional nitrogen-doped graphene foams. Issue 10 (23rd February 2018) - Li, Zihao; Li, Xianglong; Zhou, Lu; Xiao, Zhichang; Zhou, Shanke; Li, Lidong; Zhi, Linjie
Abstract : A collaborative strategy is developed for constructing stable lithium metal anodes by using a self-supporting multifunctional host matrix. Abstract : A collaborative strategy is developed for constructing stable lithium metal anodes by using self-supporting three-dimensional nitrogen-doped graphene foams as the multifunctional host matrix. The resultant electrode shows impressive electrochemical performances, attributable to the three-dimensional porous architecture and nitrogen-doping nature of such a unique host matrix.